2021
DOI: 10.3390/plants10040752
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Potato Germplasm in RDA-Genebank: Utilization for Breeding and Conservation

Abstract: Potato (Solanum tuberosum L.) is an important staple food and economic crop in many countries. It is of critical importance to understand the genetic diversity and population structure for effective collection, conservation, and utilization of potato germplasm. Thus, the objective of the present study was to investigate the genetic diversity and population structure of potato germplasm conserved in the National Agrobiodiversity Center (NAC) of South Korea to provide basic data for future preservation and breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…SSR markers are extensively utilized for DNA fingerprinting [15], parental investigations [16], genotype relocations [13] and genetic diversity analysis [12] in potatoes. According to the current status, many researchers are working on SSR markers' advancement and adaptability across potato varieties to determine their genetic diversity and achieve varietal identification [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR markers are extensively utilized for DNA fingerprinting [15], parental investigations [16], genotype relocations [13] and genetic diversity analysis [12] in potatoes. According to the current status, many researchers are working on SSR markers' advancement and adaptability across potato varieties to determine their genetic diversity and achieve varietal identification [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SSR markers are extensively utilized for DNA fingerprinting [15], parental investigation [16], genotype relocations [13], and genetic diversity analysis [12] in potatoes. According to the current status of research, many researchers are working on SSR markers' advancement and adaptability across potato varieties with respect to determining genetic diversity and varietal identification [17] The goal of the current study on potatoes is to provide basic information for the breeding of genetic resources and conservation, to explore the genetic relationships and diversity among different potato cultivars, and to perform varietal identification using SSR markers. Although numerous studies have already been reported worldwide regarding potato DNA fingerprinting, no such data is available in Pakistan to date.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that clustering of the cultivars tend to be based on their geographical origin [44]. We utilized DAPC, PCA, NJ cluster analysis, and MSN analysis to truly understand the genetic structure of these cultivars.…”
Section: Plos Onementioning
confidence: 99%
“…The level of polymorphism is based on insertion, deletion, duplication, translocation and point mutations whereas they did not affect the activity of genes (Ghareyazie et al, 1995). Properties desirable for ideal DNA markers (Jiang, 2013;Joshi et al, 2011) Genetic diversity, genetic relationships and population structure improvement, DNA fingerprinting and molecular variance, genetic variation, evolutionary relatedness in Capsicum (Lee et al, 2021;La Cruz et al, 2020;Singh et al, 2020). Sharmin et al (2018) also used SSR markers for the assessment of Genetic variability and genetic diversity in Brinjal.…”
Section: Applications Of Molecular Markers Assessment Of Genetic Dive...mentioning
confidence: 99%